Advances in Electrospun Polymer-Based Nanofibers for Wound Healing: A Narrative Review - Imanto, Teguh; Zahra, Veirda (Journal of Islamic Pharmacy, 2024)
Polymer-based nanofibers produced using electrospinning techniques have become a significant innovation in drug delivery systems, particularly in wound healing. The nanofiber structure, which resembles the extracellular matrix (ECM), provides an advantage in supporting tissue regeneration and drug release control, making it an effective solution for the treatment of acute and chronic wounds. The aim of this review is to analyze recent advancements in the use of polymer-based nanofibers for drug delivery in wound healing therapy. The method used is a systematic approach with modified PRISMA guidelines. Relevant literature was extracted from the ScienceDirect database using the keywords "polymers", "nanofiber", "electrospinning" and "wound healing," with the publication period limited to 2016–2025. From the search results that yielded 5,750 articles, a strict selection process narrowed them down to 21 relevant articles for analysis. The analysis results show that polymer-based nanofibers such as PVA, PCL, and PVP demonstrate outstanding abilities in delivering antibacterial drugs, enhancing wound healing efficiency, and combating infections, especially in chronic wounds. Nanofiber technology also provides innovative solutions in mitigating bacterial resistance. In conclusion, polymer-based nanofibers open significant opportunities in the pharmaceutical field and wound healing therapy with more precise and effective drug release control.